THICKENING THE HAIR– CAUSES, TIPS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Every woman dreams of thick and silky hair. Shampoo manufacturers promise the fairer sex that there will be no problems with shine and hair. In fact, almost every woman faces one or the other problems related to hair, and shampoos cannot solve them effectively. What to do to make the hair thicker and more beautiful? Why don't cosmetic products help?